2019
DOI: 10.1177/0003489419879716
|View full text |Cite
|
Sign up to set email alerts
|

Chronic maxillary atelectasis under the wrappings of an Egyptian mummy

Abstract: Objectives: In the context of a joint Mummy Research Project of the National Archaeological Museum, the Hellenic Institute of Egyptology and the Athens Medical Centre, an Egyptian mummy of the mid-Ptolemaic Period was transferred to our hospital and was thoroughly investigated with Computed Tomography. Methods: The mummy was carefully removed from its coffin and scanned in a 64-detector row computed tomographic scanner. Multiplanar and anthropometric measurements were obtained using advanced software. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…3a-3b] 24 , with a (cadaveric) height of 1.45 m. The CT-Scanning revealed wear in the pelvis and a post mortem dislocation of the pelvic bones. From the careful study of the results of the CT-Scanning for this mummy, one unexpected conclusion was deduced: this ancient Egyptian individual was suffering from a rare syndrome, discussed in another paper [Michailidis, Kyriazi, Maravelia et al 2019, 1165-1169, a fact proven by our unusual finding concerning the skull; that situation and the possible social implications in this person's life are thoroughly discussed in our paper [Michailidis, Kyriazi, Maravelia et. al 2019, 1167-1168.…”
Section: V2 the Case Of The Mummy Of Ta-di-thed-amūn (Aig 3346)mentioning
confidence: 83%
See 2 more Smart Citations
“…3a-3b] 24 , with a (cadaveric) height of 1.45 m. The CT-Scanning revealed wear in the pelvis and a post mortem dislocation of the pelvic bones. From the careful study of the results of the CT-Scanning for this mummy, one unexpected conclusion was deduced: this ancient Egyptian individual was suffering from a rare syndrome, discussed in another paper [Michailidis, Kyriazi, Maravelia et al 2019, 1165-1169, a fact proven by our unusual finding concerning the skull; that situation and the possible social implications in this person's life are thoroughly discussed in our paper [Michailidis, Kyriazi, Maravelia et. al 2019, 1167-1168.…”
Section: V2 the Case Of The Mummy Of Ta-di-thed-amūn (Aig 3346)mentioning
confidence: 83%
“…There was no evidence of brain removal, the brain remnants having shrunk and sunk inside the cranial cavity (Fig. 10-11) and we have observed that the ethmoid cells and the cribriform plate were intact [Michailidis, Kyriazi, Maravelia et al 2019, 1166, a fact meaning that there was no attempt of transnasal excerebration during the mummification of this particular individual, which was a very common practice in many ancient Egyptian mummies [Fanous, Couldwell 2012, 743-748;Cockburn et al 2006, 21]. According to the funerary and religious beliefs of the Egyptians, the heart ( Fig.…”
Section: V2 the Case Of The Mummy Of Ta-di-thed-amūn (Aig 3346)mentioning
confidence: 85%
See 1 more Smart Citation
“…Likewise, artificial cranial modification may have been used to identify ethnic populations, as demonstrated by Andean bio-archaeological studies. [ 10 11 12 13 14 ]…”
Section: Introductionmentioning
confidence: 99%